A high Al content RTB rare earth permanent magnet based on non-oriented diffusion and its preparation method

By adopting a non-oriented diffusion process in a rare earth permanent magnet with high Al content, a grain boundary R-rich phase with high Al content is formed, which solves the contradiction between coercive force increase and residual magnetism reduction in the prior art, and achieves the effect of high residual magnetism and high coercivity.

CN119764033APending Publication Date: 2025-04-04ZHEJIANG INNUOVO MAGNETICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411865632.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, there is a contradiction between the coercive force increase and the residual magnetization reduction during the preparation process of rare earth permanent magnets with high Al content, and it is difficult to simultaneously increase the coercive force and reduce the amount of residual magnetization reduction.

Method used

The grain boundary diffusion is performed in a magnet matrix with high Al content by using a non-oriented diffusion process. Heavy rare earth elements are added to the grain boundary diffusion on the surfaces C1 and C2 to form a grain boundary R-rich phase (H-Al phase) with high Al content to increase coercive force and reduce the reduction of residual magnetism.

Benefits of technology

Through the non-oriented diffusion process, the coercive force of the rare earth permanent magnet is improved, and the reduction of residual magnetism is effectively reduced, achieving the effect of high residual magnetism and high coercive force.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764033A_ABST
    Figure CN119764033A_ABST
Patent Text Reader

Abstract

The invention discloses a high Al content R-T-B rare earth permanent magnet based on non-oriented diffusion and a preparation method thereof. In a magnet matrix with a high Al content, non-oriented grain boundary diffusion is performed on a surface parallel to the orientation direction of the magnet, thereby increasing the coercive force of the magnet and reducing the amount of reduction in remanence, thereby obtaining an R-T-B rare earth permanent magnet with high remanence and high coercive force. The high Al content rare earth permanent magnet provided by the invention has a low magnetic permeability, reduces the magnetic coupling between main phase grains, and promotes the improvement of the matrix coercive force; the invention adopts a non-oriented diffusion method to reduce the influence of high Al grain boundaries on grain boundary diffusion, thereby improving the diffusion effect, increasing the coercive force of the magnet, and reducing the amount of remanence reduction of the magnet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth permanent magnet materials, and in particular relates to a non-oriented diffusion-based high Al content RTB rare earth permanent magnet and a preparation method and application thereof. Background Art

[0002] Grain boundary diffusion technology can effectively improve the performance of NdFeB magnets and has been widely used. After grain boundary diffusion, heavy rare earth elements (Dy / Tb, etc.) are enriched at the edge of the main phase grains to form an epitaxial shell structure, while keeping the internal composition and structure of the main phase grains basically unchanged. After the magnet is diffused through the grain boundaries, there is a concentration gradient difference along the diffusion direction. If it diffuses along the orientation direction, the finished products with different processing depths will have performance differences, affecting the performance consistency of the product.

[0003] The key factors in grain boundary diffusion technology include diffusion source composition, diffusion process and diffusion matrix. In the prior art, there are more research and development on the design of diffusion source composition and improvement and optimization of diffusion process, and less attention is paid to the composition and structural state of diffusion matrix materials. If the NdFeB magnet prepared by the double alloy process is used, there is a heavy rare earth shell in the substrate, and the presence of the shell affects the effect of grain boundary diffusion. For example, patent CN116884758A discloses a preparation method and application of a high-performance sintered NdFeB matrix magnetic sheet, which is prepared by a double alloy process, and the target product is prepared by a non-oriented grain boundary diffusion method, improving the internal coercive force gradient of the matrix magnetic sheet and optimizing the squareness. However, the thickness of the heavy rare earth shell in the magnet prepared by the double alloy process is uncontrollable and is easily affected by many factors, and the presence of the heavy rare earth shell will affect the coercive force improvement of grain boundary diffusion. Therefore, in the production process, single alloy sintered NdFeB is usually used as a grain boundary diffusion substrate.

[0004] In the existing technology, the preparation of high-performance NdFeB magnets still relies on comprehensive consideration of the blank and grain boundary diffusion process. In addition to adding heavy rare earth elements to replace Nd in the formula, other metal elements can also be added to replace Fe, such as Al. The addition of Al increases the coercivity of the magnet because some Al enters the Nd-rich phase to improve the bonding between the Nd-rich liquid phase and Nd2Fe 14 The wetting angle of the B solid phase refines the grains and reduces the size of the Nd-rich phase and the B-rich phase. The addition of Al elements to the formula not only ensures the performance of the blank, but also meets the daily use in the current production process. However, Al elements will also cause the remanence of the magnet to decrease. Therefore, the addition of Al elements in the conventional preparation process is not much. How to improve the effect of Al elements on coercivity and reduce its side effects on remanence needs further study. Summary of the invention

[0005] The purpose of the present invention is to propose a high Al content RTB rare earth permanent magnet based on non-oriented diffusion and a preparation method thereof. In a magnet matrix with a high Al content, the coercive force is further improved and the reduction of remanence is reduced by non-oriented diffusion, thereby obtaining an RTB rare earth permanent magnet with high remanence and high coercive force.

[0006] The technical solution adopted by the present invention is as follows: A high Al content RTB rare earth permanent magnet based on non-oriented diffusion, the magnet comprising the following components in mass fraction: R: 28.5wt.%~34.0wt.%, R includes R1 and RH, RH content is 0.1wt.%~10.0wt.% of the magnet mass, RH is at least one of Dy and Tb, the balance is R1, R1 is at least one of Nd, Pr, Ho,, Gd, La, Ce, Lu, Y; preferably R1 is Nd and Pr; B: 0.90wt.%~1.1wt.%, Al: 0.2~3.0wt.%, M: M is at least one of Cu, Ga, Ni, Zn, Sn, and Mn, The balance is T and other unavoidable impurities, T is Fe or Fe and Co; preferably, more than 85.0% of the mass fraction of T is Fe.

[0007] The magnet has a pair of surfaces C1 and C2 parallel to the orientation direction, and RH accounting for 0.1wt.% to 3wt.% of the mass of the magnet is added to the magnet by grain boundary diffusion on the surfaces C1 and C2.

[0008] The magnet has a pair of surfaces C1 and C2 parallel to the orientation direction, and before grain boundary diffusion, the average Al content of the surfaces C1 and C2 is lower than the average Al content of the surface of the magnet perpendicular to the orientation direction; The magnet grain boundary phase contains a high Al content grain boundary R-rich phase, which is recorded as H-Al phase. For the same magnet blank, grain boundary diffusion on surfaces C1 and C2 is recorded as a non-oriented diffused magnet, and grain boundary diffusion on the oriented surface is recorded as an oriented diffused magnet. The average Al element content of the H-Al phase on the diffusion surfaces C1 and C2 of the non-oriented diffused magnet is lower than the average Al element content of the H-Al phase on the diffusion surface of the oriented diffused magnet.

[0009] The surfaces C1 and C2 are a pair of parallel planes. In the present invention, surfaces C1 and C2 can be considered parallel when the angle between the two surfaces is between 0 and 3 degrees. Surfaces C1 and C2 are not adjacent.

[0010] In the magnet, the Al content is preferably 0.2-1.5 wt.%, more preferably 0.2-0.5%.

[0011] RH accounting for 0.1wt.%~3wt.% of the magnet mass is added to the magnet by grain boundary diffusion.

[0012] The angle between the surface C1 or C2 and the orientation direction is between 0 and 3 degrees.

[0013] The magnet grain boundary phase contains a high Al content grain boundary R-rich phase (H-Al phase), and the average Al element content of the H-Al phase on the surfaces of the magnets C1 and C2 is lower than the average Al element content of the H-Al phase on the orientation surface of the magnet.

[0014] The magnet orientation plane refers to the surface of the magnet that is perpendicular to the orientation direction.

[0015] The Al content in the high Al content grain boundary R-rich phase in the magnet is 3.0-30 wt.%, preferably 3-6%.

[0016] The high Al content RTB rare earth permanent magnet based on non-oriented diffusion can be prepared by the following method: A heavy rare earth element diffusion source containing RH is coated on the C1 and C2 surfaces of the pre-diffusion sheet parallel to the orientation direction, and then a grain boundary diffusion treatment is performed. After cooling, an aging treatment is performed, and a secondary processing is performed to obtain a finished magnetic sheet, thereby obtaining the RTB rare earth permanent magnet with high squareness.

[0017] The pre-diffusion sheet is generally a large piece of magnet obtained by machining the RTB magnet matrix and cutting it along the direction parallel to the orientation, so that the pre-diffusion sheet has at least one pair of surfaces C1 and C2 parallel to the magnet orientation direction. The magnet after machining generally needs to be cleaned. Furthermore, after machining, ultrasonic cleaning, pickling, sandblasting, etc. can be used to remove surface impurities such as oil stains and rust spots on the magnet surface.

[0018] The height dimension of the pre-diffusion sheet along the orientation direction may be X times the height dimension of the target magnetic sheet along the orientation direction, where 1≤X≤20.

[0019] The present invention also provides a method for preparing a high Al content RTB rare earth permanent magnet based on non-oriented diffusion, the method comprising: The RTB magnet substrate is machined and cut along a direction parallel to the orientation to obtain a large piece of magnet as a pre-diffusion sheet, so that the pre-diffusion sheet has at least one pair of surfaces C1 and C2 parallel to the orientation direction of the magnet; a heavy rare earth element diffusion source containing RH is coated on the surfaces C1 and C2 of the pre-diffusion sheet parallel to the orientation direction, and then a grain boundary diffusion treatment is performed, and an aging treatment is performed after cooling, and then a secondary processing is performed to obtain a finished magnetic sheet, thereby obtaining the RTB rare earth permanent magnet with high squareness.

[0020] The height dimension of the pre-diffusion sheet along the orientation direction may be X times the height dimension of the target magnetic sheet along the orientation direction, where 1≤X≤20.

[0021] The RTB magnet matrix is ​​prepared according to a conventional preparation method, by taking raw materials according to the magnet matrix ratio, and by melt-spinning SC sheets, hydrogen crushing, air flow milling, orientation molding, isostatic pressing, vacuum sintering and aging treatment.

[0022] The diffusion source containing the RH heavy rare earth element may be a pure metal, alloy, oxide, fluoride or a mixture thereof containing the RH heavy rare earth element.

[0023] The coating of the heavy rare earth element diffusion source containing RH can be carried out by PVD, spraying, printing and the like.

[0024] In the method, the temperature of grain boundary diffusion is 800° C. to 950° C., and the holding time is 10 to 30 hours.

[0025] The temperature of aging treatment is 460~540℃ and the time is 2~10h.

[0026] The grain boundary diffusion treatment and the tempering treatment are both performed in a vacuum environment.

[0027] The beneficial effects of the present invention are: The rare earth permanent magnet with high Al content provided by the present invention has low magnetic permeability, reduces the magnetic coupling between the main phase grains, and promotes the improvement of the matrix coercivity; part of Al enters the Nd-rich liquid phase and reacts with Nd2Fe 14 The wetting angle of the B solid phase refines the grains, while reducing the size of the Nd-rich phase and the B-rich phase, thereby improving the coercivity of the matrix.

[0028] Rare earth permanent magnets with high Al content are prone to generate high Al grain boundary phases, and the distribution of this grain boundary phase is anisotropic, with more distribution along the orientation direction of the magnet and less distribution along the surface perpendicular to the orientation direction; the present invention adopts a non-oriented diffusion method to reduce the influence of high Al grain boundaries on grain boundary diffusion, thereby improving the diffusion effect, increasing the coercive force of the magnet, and reducing the drop in the residual magnetism of the magnet.

[0029] Rare earth permanent magnets with high Al content enhance the fluidity of the grain boundary phase, prompting the diffusion source to more continuously wrap the main phase grains, further improving the coercive force, and the diffusion source after diffusion is more continuously and clearly enriched at the grain boundary. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a backscattered electron image of the diffusion surface of the magnet obtained after orientation diffusion treatment in Example 3 of the present invention.

[0031] Figure 2This is a backscattered electron image of the diffusion surface of the magnet obtained after non-oriented diffusion treatment in Example 3 of the present invention.

[0032] Figure 3 This is a backscattered electron image of the diffusion surface of the magnet obtained after non-oriented diffusion treatment in Example 5 of the present invention. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0034] Examples 1-5 and Comparative Examples 1-2 Comparative Examples 1-2 and Examples 1-5 respectively prepared raw materials according to the composition table in Table 1 (in wt.%), and prepared sintered NdFeB magnets using the following preparation method: The prepared raw materials are prepared into powders with SMD=3.0 μm through melting in a smelting furnace, hydrogen crushing and air flow grinding.

[0035] The obtained air flow milled powder is oriented and formed, and isostatically pressed to obtain a green body. The green body is vacuum sintered at 1085℃*8h, and heat treated at 880℃*3h and 520℃*3h to prepare a blank. The blank size is 73*54*36 (unit: mm), of which 36mm is the orientation direction, and the sizes represent the sizes in the x-, y-, and z-axis directions in sequence.

[0036] Take a blank and divide it into two small pieces, each of which is cut into slices with a thickness of 5 mm, one of which is cut in a direction parallel to the orientation direction, and the slice size is 5*54*36 (unit: mm), and the sizes represent the sizes in the x, y, and z axes respectively; the other is cut in a direction perpendicular to the orientation direction, and the slice size is 36*54*5 (unit: mm), and the sizes represent the sizes in the x, y, and z axes respectively; all substrate slices are cleaned by acid pickling, ultrasonic water washing, drying, sandblasting and other steps to obtain a diffusible substrate black sheet, the slice cut parallel to the orientation direction, i.e., the non-oriented surface slice, is recorded as black sheet A1; the slice cut perpendicular to the orientation direction, i.e., the oriented surface slice, is recorded as black sheet B1.

[0037] Tb powder, pinene alcohol and polyvinyl butyral were mixed in a mass ratio of 70:20:10 to prepare a slurry to obtain a diffusion source.

[0038] Use automatic spraying equipment to evenly spray the diffusion source onto the black substrate A1 and B1. The spraying surface of A1 is 54*36 (unit: mm) (parallel to the orientation direction), and the spraying surface of B1 is 54*36 (unit: mm) (perpendicular to the orientation direction). After spraying, the single piece is dried and then turned over for spraying and drying. The average total weight gain of the single piece is 0.65%. The non-oriented magnetic sheet after double-sided spraying and drying is recorded as A2; the oriented magnetic sheet is recorded as B2.

[0039] The sprayed magnetic sheets are stacked and placed in a vacuum heat treatment furnace. After heat treatment at 900℃*25h and 520℃*6h, they are processed again to the target size of 5*9*5 (in mm). The product magnet obtained from A2 is recorded as A3, which is a non-oriented magnet; the product magnet obtained from B2 is recorded as B3, which is an oriented magnet.

[0040] Table 1: Raw material composition of the magnet matrix of Comparative Examples 1-2 and Examples 1-5 (in wt.%) Nd Pr Dy Co B Ga Al Zr Fe Comparative Example 1 20.4 6.8 2.5 1 0.96 0.1 0 0.15 margin Comparative Example 2 20.4 6.8 2.5 1 0.96 0.1 0.1 0.15 margin Example 1 20.4 6.8 2.5 1 0.96 0.1 0.2 0.15 margin Example 2 20.4 6.8 2.5 1 0.96 0.1 0.5 0.15 margin Example 3 20.4 6.8 2.5 1 0.96 0.1 1.5 0.15 margin Example 4 20.4 6.8 2.5 1 0.96 0.1 3 0.15 margin Example 5 20.4 6.8 2.5 1 0.96 0.1 4.5 0.15 margin The pre-diffusion substrates and post-diffusion products A3 and B3 prepared in the above comparative examples 1-2 and examples 1-5 were subjected to magnetic property tests to obtain remanence and coercivity. The test results are shown in Table 2 Table 2: Performance table of sample magnets of Comparative Examples 1-2 and Examples 1-5 From the results in Table 2, it can be seen that: when the Al content is less than 0.2%, the oriented diffusion process is better than the non-oriented diffusion process, and the coercive force increase of the oriented diffusion process is greater, but the remanence decrease of the oriented diffusion process is greater; when the Al content is ≥0.2%, the coercive force increase of the non-oriented diffusion process is better than that of the oriented diffusion process, and the remanence decrease is significantly lower than that of the oriented diffusion process; but when the Al content is ≥3%, the coercive force increase of the oriented and non-oriented processes is low, and the effects are not good.

[0041] The sample magnets of Comparative Examples 1-2 and Examples 1-5 were subjected to microstructural analysis and composition analysis using a JEOL scanning electron microscope; Figure 1 and Figure 2 They are backscattered electron images of the oriented diffuse magnet and the non-oriented diffuse magnet samples of Example 3, Figure 3 This is a backscattered electron image of the non-oriented diffused magnet sample of Example 5. In Comparative Example 1-2, substantially no H-Al phase is observed.

[0042] Figure 1 The dotted line in the middle shows the electron microscope image of the microstructure of the H—Al phase in any area of ​​the diffusion surface of the magnet B3 prepared by the oriented diffusion process in Example 3. Figure 2 The dotted line in the middle shows the microstructure electron microscope image of the H-Al phase in any area of ​​the diffusion surface of the magnet A3 prepared by the non-oriented diffusion process in Example 3. By analyzing the Al content in the H-Al phase in multiple locations in the magnet and calculating the area of ​​the grain boundary phase region where the H-Al accounts for, the H-Al phase proportion of the oriented diffusion magnet is H1, and the H-Al phase proportion of the non-oriented diffusion magnet is H2, and the results are shown in Table 3. It can be seen from Table 3 that the H-Al phase of the oriented diffusion magnet occupies a large area of ​​the grain boundary phase, and the H-Al phase of the non-oriented surface diffusion process occupies a small area of ​​the grain boundary phase.

[0043] Figure 3 The dotted line in the middle shows the electron microscope image of the microstructure of the H-Al phase in any area of ​​the diffusion surface of the magnet prepared by the non-oriented diffusion process in Example 5. By analyzing the Al content in the H-Al phase in multiple locations in the magnet and calculating the area of ​​the grain boundary phase region where the H-Al ratio is located, the H-Al phase ratio H3 of the non-oriented diffusion magnet is calculated, and the results are shown in Table 3.

[0044] Table 3: H-Al ratio and Al content of diffusion products A3 and B3 of Examples 3 and 5.

[0045] From the above analysis, it can be seen that for the same magnet blank, the Al content in the H-Al phase of the NdFeB magnet prepared by the non-oriented diffusion process of the present invention is in line with the scope of the present invention; while the Al content in the H-Al phase on the diffusion surface of the NdFeB magnet prepared by the oriented diffusion process is higher than the Al content in the H-Al phase on the diffusion surface of the non-oriented diffusion magnet. In Example 5, the Al content in the magnet matrix is ​​too high, resulting in too much H-Al phase in the diffusion surface, a high Al content in the H-Al phase, a poor diffusion process, and a small increase in the coercive force of the magnet. In Comparative Examples 1-2, the Al content in the raw materials is lower than the design lower limit of the raw materials of 0.2wt.%, so no H-Al phase can be observed in the scanning electron microscope observation.

[0046] The oriented surface section and the non-oriented surface section of the same blank in Examples 3 and 4 were taken for EPMA surface scanning analysis, and the average Al content of 10 scanning results was calculated. The test results are shown in Table 4.

[0047] Table 4: Surface Al content of black sheets A1 and B1 of Examples 3 and 4.

[0048] It can be seen from Table 4 that the average Al content of the non-oriented surface of the magnets of Examples 3 and 4 is lower than the average Al content of the oriented surface; the use of non-oriented diffusion is beneficial to the grain boundary diffusion effect of high Al content magnets.

Claims

1. A high Al content RTB rare earth permanent magnet based on non-oriented diffusion, characterized in that The magnet includes the following components in mass fractions: R: 28.5wt.%~34.0wt.%, R includes R1 and RH, RH content is 0.1wt.%~10.0wt.% of the magnet mass, RH is at least one of Dy and Tb, the balance is R1, R1 is at least one of Nd, Pr, Ho, Gd, La, Ce, Lu, Y; B: 0.90wt.%~1.1wt.%, Al: 0.2~3.0wt.%, M: M is at least one of Cu, Ga, Ni, Zn, Sn, and Mn, The balance is T and other unavoidable impurities, T is Fe or Fe and Co; The magnet has a pair of surfaces C1 and C2 parallel to the orientation direction, and RH accounting for 0.1wt.% to 3wt.% of the mass of the magnet is added to the magnet by grain boundary diffusion on the surfaces C1 and C2.

2. The high Al content RTB rare earth permanent magnet based on non-oriented diffusion according to claim 1, characterized in that: The magnet has a pair of surfaces C1 and C2 parallel to the orientation direction, and before grain boundary diffusion, the average Al content of the surfaces C1 and C2 is lower than the average Al content of the surface of the magnet perpendicular to the orientation direction; The magnet grain boundary phase contains a high Al content grain boundary R-rich phase, which is recorded as H-Al phase. Grain boundary diffusion on surfaces C1 and C2 is recorded as a non-oriented diffused magnet, and grain boundary diffusion on the oriented surface is recorded as an oriented diffused magnet. The average Al element content of the H-Al phase on the diffusion surfaces C1 and C2 of the non-oriented diffused magnet is lower than the average Al element content of the H-Al phase on the diffusion surface of the oriented diffused magnet.

3. The high Al content RTB rare earth permanent magnet based on non-oriented diffusion according to claim 1, characterized in that: The surfaces C1 and C2 are a pair of parallel planes; the surfaces C1 and C2 are not adjacent.

4. The high Al content RTB rare earth permanent magnet based on non-oriented diffusion according to claim 1, characterized in that: In the magnet, the Al content is 0.2-1.5wt.%.

5. The high Al content RTB rare earth permanent magnet based on non-oriented diffusion according to claim 1, characterized in that: The Al content in the high Al content grain boundary R-rich phase in the magnet is 3.0-30 wt.%.

6. The high Al content RTB rare earth permanent magnet based on non-oriented diffusion according to any one of claims 1 to 5, characterized in that: The non-oriented diffusion-based high Al content RTB rare earth permanent magnet is prepared by the following method: A heavy rare earth element diffusion source containing RH is coated on the C1 and C2 surfaces of the pre-diffusion sheet parallel to the orientation direction, and then a grain boundary diffusion treatment is performed, and an aging treatment is performed after cooling, and then a secondary processing is performed to obtain a finished magnetic sheet, thereby obtaining the RTB rare earth permanent magnet with high squareness; The pre-diffusion sheet is a large piece of magnet obtained by machining the RTB magnet substrate and cutting it along a direction parallel to the orientation direction, so that the pre-diffusion sheet has at least one pair of surfaces C1 and C2 parallel to the magnet orientation direction.

7. The method for preparing a high Al content RTB rare earth permanent magnet based on non-oriented diffusion according to any one of claims 1 to 5, characterized in that: The method is: The RTB magnet substrate is machined and cut along a direction parallel to the orientation to obtain a large piece of magnet as a pre-diffusion sheet, so that the pre-diffusion sheet has at least one pair of surfaces C1 and C2 parallel to the orientation direction of the magnet; a heavy rare earth element diffusion source containing RH is coated on the surfaces C1 and C2 of the pre-diffusion sheet parallel to the orientation direction, and then a grain boundary diffusion treatment is performed, and an aging treatment is performed after cooling, and then a secondary processing is performed to obtain a finished magnetic sheet, thereby obtaining the RTB rare earth permanent magnet with high squareness.

8. The method according to claim 7, characterized in that The height dimension of the pre-diffusion sheet along the orientation direction is X times the height dimension of the target magnetic sheet along the orientation direction, 1≤X≤20.

9. The method according to claim 7, characterized in that The RTB magnet matrix is ​​prepared by taking raw materials according to the magnet matrix ratio, and performing melt-throwing of SC sheets, hydrogen crushing, air flow milling, orientation molding, isostatic pressing, vacuum sintering and aging treatment.

10. The method according to claim 7, characterized in that In the method, the temperature of grain boundary diffusion is 800° C. to 950° C., and the holding time is 10 to 30 hours.